What are the Expectations of Tourists from Homestay Accommodation: Assessing the Satisfaction Level of Tourists Staying in Homestays - Singh, Ritika; Sajnani, Manohar; Gupta, Pawan (Journal of Rural Development, 2022)
Modern tourists are more interested in value-seeking, gaining experiences and exploring personal interests rather than a mere sedentary travel. An alternative form of accommodation, especially homestays in rural areas enable tourists to experience authentic culture, tradition, lifestyle as well as local cuisines and a serene environment to replenish their mind and soul. The objective of the study is to assess the variation between expectations and satisfaction of tourists staying in homestays and the relationship between the levels of expectation of tourists staying in homestays and tourists not staying in homestays. The study has been conducted in the rural areas of the Kullu District of Himachal Pradesh, India. The data has been collected through a questionnaire method from a sample of 300 tourists. Significant attributes of homestay have been identified with the help of principal component analysis with a varimax rotation, that categorised all the variables in 5 factors, namely Accommodation, Host, Amenities & Services, Safety & Security and Information. The author found that there is a significant difference between the levels of expectation and the level of satisfaction of tourists staying in the homestay and also between the expectation level of tourists’ staying in a homestay and the level of expectation of tourists’ not staying in a homestay. The level of expectation is greater than the level of satisfaction of tourists staying in a homestay for all the variables except for the variable ‘Host’. Tourists staying in homestay unveil that their level of satisfaction is greater than level of expectation for the variable-‘Host’. There is strong positive correlation between level of expectation of tourists’ staying in homestay and the level of expectation of tourists’ not staying in homestay for the variable- ‘Host’. The research purpose is to assess the expectation of tourists and their satisfaction through multi-dimensional attributes of homestay accommodation. The study also evaluates the expectation of potential homestay guests (tourists). The research is intended to promote rural Homestay accommodation in India as well as assist homestay owners to act upon the customization of services and facilities for their existing as well as potential guests by adapting to changes according to the needs and demands of the guests, and also emphasise the need for concerned authorities to undertake necessary development in the region for promotion of rural tourism.